2007
DOI: 10.1111/j.1475-097x.2007.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological determinants of the variation in left ventricular mass from early adolescence to late adulthood in healthy subjects

Abstract: CorrigendumPhysiological determinants of the variation in left ventricular mass from early adolescence to late adulthood in healthy subjects. Clin Physiol Funct Imaging (2005), Cain et al.The above mentioned article 1 contained the errors listed below. The authors identified these errors during the process of writing a second article based on the same study population.Following these changes, all levels of statistical significance were effectively unchanged and the conclusions remained unchanged. 1. Age was er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Curve estimation and the 95% prediction intervals of LVM, dimensions, and function were defined using commercial software (Matlab curve fitting toolbox, Matlab version R12, Mathworks). The most appropriate curve fitting algorithm for LVM, dimensions and functional measures was identified as the rational polynomial of the form P(x)/Q(x) where both numerator and denominator were at most of the second degree and which had the highest adjusted R 2 and lowest root mean square (RMS) of the error [14]. The predicted lower, mean and upper limits for normal values of LV parameters in each decade were calculated as the average of the mean and 95% prediction interval of the predicted values for each whole year as given by the curve estimation model.…”
Section: Methodsmentioning
confidence: 99%
“…Curve estimation and the 95% prediction intervals of LVM, dimensions, and function were defined using commercial software (Matlab curve fitting toolbox, Matlab version R12, Mathworks). The most appropriate curve fitting algorithm for LVM, dimensions and functional measures was identified as the rational polynomial of the form P(x)/Q(x) where both numerator and denominator were at most of the second degree and which had the highest adjusted R 2 and lowest root mean square (RMS) of the error [14]. The predicted lower, mean and upper limits for normal values of LV parameters in each decade were calculated as the average of the mean and 95% prediction interval of the predicted values for each whole year as given by the curve estimation model.…”
Section: Methodsmentioning
confidence: 99%
“…for men and 104 g/m 2 for women). The mean LV mass (LVM) indexed by BSA in the subsample of healthy individuals (20 men and 20 women, mean age = 48 yrs) was 57 and 42 g/m 2 , respectively, which are quite discordant values in comparison to the international literature [16][17][18][19] . However, these measurements are similar to the findings of Ghorayeb et al 22 , who reported a mean LVM of 57 g/m 2 in a sample of 30 normal men evaluated by CMR.…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, our data suggest that the values of cardiac mass measured in our population through CMR 22 can be underestimating the actual mass of the organ between 24% and 60% in comparison to the LVM estimated by CMR reported in international studies [16][17][18][19] . When we compare the mean LVM estimated by CMR with those obtained at the necropsy, this underestimation reaches even higher values.…”
mentioning
confidence: 93%
“…Echographically measured left ventricular mass is an important predictor of adverse events in the general population [7]. LV mass is associated with multiple factors including age, blood pressure, BMI, and sex [811]. Regular physical exercise is also associated with LV mass increase [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases related to occupational stress is also scientifically known [3]. Scientists have been interested in echocardiographic and cardiovascular variations due to exposure to lead [4–8]. William Ogle [6] observed the first, in the years eighties the effect of heavy work on heart.…”
Section: Introductionmentioning
confidence: 99%